'Let me in! A comment on insider research'. Issue 1 (2nd January 2017) - Ellis-Caird, Helen
Abstract: This issue of EJPC foregrounds the work of insider researchers investigating clinical practice in an array of contexts including one-to-one work with trauma, group work with those who have been abused, adoptive family work and work with a home treatment team and inpatient team. In this comment piece, I consider the papers from an outsider's perspective and apply a quality lens to gain a surer hold of what the papers can offer. I've highlighted the rich resonance of many of the accounts, but also the specialist language in which most are written, and the lack of space for discussion of the process of research or analysis of data conducted. I argue that this creates barriers in the way of these papers being consumed, understood and applied by a wider audience, which may mean that the impact and implications of the work are not fully realised.